New dammarane-type triterpene saponins from Gynostemma pentaphyllum and their anti-hepatic fibrosis activities in vitro. (June 2018) - Shi, Guohui; Wang, Xude; Zhang, He; Zhang, Xiaoshu; Zhao, Yuqing
Graphical abstract: Highlights: Gynostemma pentaphyllum is used as a functional food in China for long. Three new dammarane-type saponins were discovered from G. pentaphyllum . Compound27 exhibited the highest activity with an IC50 value of 24.4 μM. G. pentaphyllum can be developed as a liver protective functional food. Abstract: Jiaogulan ( Gynostemma pentaphyllum ) tea as one functional food has been commercially available over the world. In this study, the chemical constituents and health properties of Gynostemma pentaphyllum ( G. pentaphyllum ) has been investigated. Three new dammarane-type triterpenes Gypenoside C, Gypenoside D, Gypenoside E as well as twenty-four known compounds were isolated from the total G. pentaphyllum saponins. The structural determination was accomplished with spectroscopic analysis, in particularly 1D, 2D-NMR and HRESIMS. All the isolated compounds were evaluated for inhibition activities of the growth of human Hepatic Stellate Cells (t-HSC/Cl-6) and compounds2, 9, 10, 17, 24, 25, 26, 27 showed significant cytotoxic activities. Among them, compound27 exhibited more excellent inhibitory activities whose IC50 value (24.4 μM) was 10-fold lower than positive control silymarin. The discovery of new t-HSC/Cl-6 inhibitors from G. pentaphyllum expands its usage as a functional food.